Effects of different larenageal mask types on hemodynamics and airway in pediatric - Hatice Selcuk Kusderci; Mesut Oterkus (Medicine Science, 2022)
In pediatric cases, as in adults, supraglottic airway devices (SADs) are common in short-term interventions. We aimed to investigate the effects of these supraglottic airway devices, which we use in pediatric cases, on hemodynamic and airway in our study, in which we used four types of SAD: The LMA Classic, Cobra Perilaryngeal Airway (PLA), İ-gel LMA, and Ambu® AuraGain. 103 patients with ASA 1-2 and under 18 years of age were randomly divided into LMA Classic, Cobra PLA, i-Gel LMA, and Ambu LMA. The demographic data of the patients were recorded. Hemodynamic data, SAD insertion durations, Pre-operative End-tidal CO2, and airway pressures were recorded at induction, intubation (during SAD insertion), and peri-operative 1st, 2nd, 3rd, 4th, 5th, and 10th minutes. As a result of our study, the groups had similar HR and SpO2 values. EtCO2 values were generally similar to the LMA Classic group in cobra PLA. When compared to i-gel LMA and Ambu LMA, Cobra PLA EtCO2 values were high but within the clinically acceptable range as well. Likewise, airway pressures were not statistically different from the classical LMA Cobra PLA. Airway pressure was higher in the Cobra PLA group than in I-Gel LMA and Ambu LMA. However, it was lower than 20 mm H2O. In pediatric cases, LMA Classic, Cobra PLA, I-gel LMA, and Ambu LMA can be used safely in general. However, we think that airway pressures should be followed-up more closely in the use of Cobra PLA. [Med-Science 2022; 11(1.000): 166-70]